Single-actuator AUV performing 3-DOF motion. (3rd March 2020) - Kunimatsu, Kei; Hattori, Yuya; Kurabayashi, Daisuke
Abstract : In this study, we aim to design, simulate and build an autonomous underwater robot with constrained number of control input. A one degree-of-freedom (DOF) input robot whose control output come in three-DOF underwater position is created and tested through simulation and experiment. The robot has a tube-like shape with a vertical pathway inside for pushing water through using a motorized propeller as its only actuator, making '1-DOF input'. Despite constraining to one actuator, three different patterns of input by the difference of motor actuation are used to get various output underwater. When the motor rotates forward, the water is pushed upward and the robot moves downward. With backward rotation, the robot rotates around the vertical axis to change orientation. Lastly, when the motor stops, the robot floats with strong buoyancy. In addition, some weights are placed on its body for asymmetrical trajectory. Following a formation of design and mechanism, a model is derived. A simulation is carried out to verify the ability of the proposed model. Then, a test robot is built and tested in a real water tank. Both the simulation and experiment results support the proposal, showing that the robot can travel in 3-DOF with the limited inputs. GRAPHICAL ABSTRACT: